Effects of Nitrogen Rates and Time of Application on Yield of Maize: Rainfall Variability Influenced Time of N Application - Zerihun Abebe; Hailu Feyisa (International Journal of Agronomy)
Despite the fact that maize productivity is relatively better than other major cereal crops, its current productivity is still far below its potential productivity. N rate and time of application are among the major abiotic factors limiting the productivity of the crop. Because of such gaps, the experiment was conducted at Bako Agricultural Research Center in 2013 and 2014 cropping seasons to determine optimum N rate and time of application. Four levels of N rates (46, 69, 92, and 115 N kg ha−1) and four levels (T1, T2, T3, and T4) of different time of N application were arranged in factorial combinations. Moreover, previously recommended N and the control were arranged in a randomized complete block design with three replications. In 2013, the highest significant biomass yield (21.2 tha−1) was obtained at 115 N kg ha−1 and T4 followed by 69 N kg ha−1 at T1 and T2 and 92 N kg ha−1 at T2. In contrast, the highest grain yield in 2013 was obtained at 92 N kg ha−1 at T2 followed by 115 N kg ha−1 at either T2 or T4 and 69 N kg ha−1 at either T1 or T3 application time. Interestingly, a significant yield increase by 37% was obtained when 92 N kg ha−1 at the time of T2 was applied compared to previous recommended 110 N kg ha−1 rate and time of application. In 2014, however, the highest yield was recorded when 92 N kg ha−1 at T1 was used. Application of 46 N kg ha−1 at T2 showed statistically similar yield performance when compared with previous N recommendation. The lowest yield was recorded from the control plot in both years. In 2013, the maximum net profit and acceptable marginal rate of return (MMR) were obtained when 92 N kg ha−1 at T2 was used for maize production during erratic and heavy rainfall distribution, particularly at a time of N application. However, the maximum net benefit (30743 ETB ha−1) and acceptable MRR could be obtained when 92 N kg ha−1 at T1 was used if the rainfall amount and distribution are relatively uniform. In conclusion, application of 92 N kg ha−1 at T1 (10–15 DAP and 35–40 DAP) is the best N rate and time of application in good rainy seasons and hence recommended for the end users. However, in the case of erratic and heavy rainy seasons, application of 92 N kg ha−1 at three times application regimes (1/3 N at 10–15 days after planting (DAP), 1/3 N at 35–40 DAP and 55–60 DAP) should be used to get maximum profit and acceptable MRR.